2021
DOI: 10.2337/db21-0110
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Podocyte Translatome During Development of Type 2 and Type 1 Diabetic Nephropathy Using Podocyte-Specific TRAP mRNA RNA-seq

Abstract: Podocyte injury is important in development of diabetic nephropathy (DN). Although several studies have reported single-cell-based RNA sequencing (RNA-seq) of podocytes in type 1 DN (T1DN), the podocyte translating mRNA profile in type 2 DN (T2DN) has not previously been compared with that of T1DN. We analyzed the podocyte translatome in T2DN in podocin-Cre; Rosa26 fsTRAP ; eNOS 2/2 ; db/db mice and compared it with that of streptozotocininduced T1DN in podocin-Cre; Rosa26 fsTRAP ; eNOS 2/2 mice using translat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…To identify the candidate genes involved in podocyte damage in DKD progression, we used the single-nucleus RNA sequencing (snRNA-seq) database from kidney of DKD patients to screen differentially expressed genes. Consistent with the results reported in previous studies, [15][16][17][18] the downregulated molecule membrane-associated guanylate kinase inverted 2 (MAGI2) was specific expression in podocytes and correlated with podocyte loss in DKD. MAGI2, a member of the MAGUK family of scaffolding proteins, contains 5 PDZ domains, 2 WW domains, an SH3 domain, and a catalytically inactive guanylate kinase domain.…”
Section: Introductionsupporting
confidence: 90%
“…To identify the candidate genes involved in podocyte damage in DKD progression, we used the single-nucleus RNA sequencing (snRNA-seq) database from kidney of DKD patients to screen differentially expressed genes. Consistent with the results reported in previous studies, [15][16][17][18] the downregulated molecule membrane-associated guanylate kinase inverted 2 (MAGI2) was specific expression in podocytes and correlated with podocyte loss in DKD. MAGI2, a member of the MAGUK family of scaffolding proteins, contains 5 PDZ domains, 2 WW domains, an SH3 domain, and a catalytically inactive guanylate kinase domain.…”
Section: Introductionsupporting
confidence: 90%
“…This mouse line has features similar to that from the Jackson Laboratory ( ): Significant increases in the body weight starting at 4 wk, hyperglycemia (6-h fasting blood glucose and hemoglobin A1c) at 8 wk, insulinemia (> 3-fold) at 8 wk, and hyperlipidemia (cholesterol, triglyceride, and low-density lipoprotein) along with the early onset of renal dysfunction (indicated by significantly increased microalbumin level in 24-h urine analysis) at 12 wk of age. Therefore, this mouse line has been widely used as a model for studies on type 2 diabetes[ 19 , 20 ], including for the studies on DN of type 2 diabetes[ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that clopidogrel significantly reduced renal collagen and fibronectin (FN) expression and thus ameliorated diabetes-induced renal fibrosis in a streptozotocin-induced murine model of type 1 diabetes[ 17 ]. However, because 80%-90% of the population with diabetes has type 2 disease[ 1 ], in the present study, we aimed to determine whether clopidogrel treatment has a preventive or therapeutic effect in the kidneys of obese type 2 diabetic db / db mice, a widely used mouse model of type 2 diabetes for DN investigations[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decreased number of podocytes is associated with proteinuria and glomerular structural damage in diabetic nephropathy [ 105 , 106 ]. Podocyte apoptosis and the subsequent podocyte depletion may indeed represent early events affecting the diabetic kidney and underlying diabetic glomerulopathy, which leads to diabetic nephropathy in type I and type II diabetes [ 107 , 108 ]. Podocyte apoptosis coincides with the onset of diabetes and hyperglycemia in type I and type II diabetes, indicating that glucotoxicity may be underlying the stimulation of pro-apoptotic signaling and subsequent podocyte injury in diabetic kidneys.…”
Section: Apoptosis In Diabetic Nephropathymentioning
confidence: 99%